Psychometric properties and criterion related validity of the Norwegian version of hospital survey on patient safety culture 2.0 - Espen Olsen; Seth Ayisi Junior Addo; Susanne Sørensen Hernes; Marit Halonen Christiansen; Arvid Steinar Haugen; Ann-Chatrin Linqvist Leonardsen (BMC, 2024)
Abstract Background Several studies have been conducted with the 1.0 version of the Hospital Survey on Patient Safety Culture (HSOPSC) in Norway and globally. The 2.0 version has not been translated and tested in Norwegian hospital settings. This study aims to 1) assess the psychometrics of the Norwegian version (N-HSOPSC 2.0), and 2) assess the criterion validity of the N-HSOPSC 2.0, adding two more outcomes, namely 'pleasure of work' and 'turnover intention'. Methods The HSOPSC 2.0 was translated using a sequential translation process. A convenience sample was used, inviting hospital staff from two hospitals (N = 1002) to participate in a cross-sectional questionnaire study. Data were analyzed using Mplus. The construct validity was tested with confirmatory factor analysis (CFA). Convergent validity was tested using Average Variance Explained (AVE), and internal consistency was tested with composite reliability (CR) and Cronbach's alpha. Criterion related validity was tested with multiple linear regression. Results The overall statistical results using the N-HSOPSC 2.0 indicate that the model fit based on CFA was acceptable. Five of the N-HSOPSC 2.0 dimensions had AVE scores below the 0.5 criterium. The CR criterium was meet on all dimensions except Teamwork (0.61). However, Teamwork was one of the most important and significant predictors of the outcomes. Regression models explained most variance related to patient safety rating (adjusted R2 = 0.38), followed by 'turnover intention' (adjusted R2 = 0.22), 'pleasure at work' (adjusted R2 = 0.14), and lastly, 'number of reported events' (adjusted R2=0.06). Conclusion The N-HSOPSC 2.0 had acceptable construct validity and internal consistency when translated to Norwegian and tested among Norwegian staff in two hospitals. Hence, the instrument is appropriate for use in Norwegian hospital settings. The ten dimensions predicted most variance related to 'overall patient safety', and less related to 'number of reported events'. In addition, the safety culture dimensions predicted 'pleasure at work' and 'turnover intention', which is not part of the original instrument.